High humidity-sensitive discoloration materials fabricated with pH indicator ingredients. (November 2021) - Zhang, Jinju; Tan, Jialing; Chen, Xin; Yin, Yunjie; Wang, Chaoxia
Abstract: A humidity-sensitive discoloration polyester fabric induced by pH indicator cresol red/thymol blue is prepared via a facial screen printing. Boric acid can adjust the pH of the system as the humidity changes, thereby affecting the discoloration of cresol red/thymol blue. Silica gel and hydrophilic silica aerogel with porous structure are used as high-performance hygroscopic agent. The prepared humidity-sensitive discoloration cresol red/thymol blue polyester fabric (CRP/TBP) displays rapid response to relative humidity (RH) change and exhibits obvious color change. As humidity increases, the prepared discoloration polyester fabric shows multiple colors, of which the absorption peaks of CRP and TBP in the visible light range shifted from 430 nm to 440 nm–520 nm and 550 nm, respectively. The steady discoloration performance in the moisture absorption/drying process is observed after 25 cycles, pointing out good reversibility and repeatability of humidity-sensitive discoloration polyester fabric. Considering these excellent properties, humidity-sensitive discoloration polyester fabrics are promising as sensitive RH detector with potential application in colorimetric sensors, decorative coatings and anti-counterfeiting technology. Graphical abstract: Image 1 Highlights: The color change of prepared humidity-sensitive discoloration polyester fabric is induced by the proton transfer between pH indicator ingredients. The prepared humidity-sensitive discoloration polyester fabric shows multiple colors upon exposure to different RH. The prepared humidity-sensitive discoloration polyester fabric possess good reversibility and repeatability. The porous structure of hydrophilic silica aerogel and silica gel attribute to humidity sensitivity of humidity-sensitive discoloration polyester fabric, realizing real-time humidity monitoring. Polyester has low moisture regain, showing superior response to humidity changes.